PRAKTEK WINDOW DRESSING PADA REKSA DANA SAHAM DI INDONESIA TAHUN 2008-2012 - Sia Olinda Christina; Roos K Andadari (Kompetensi (Competence : Journal of Management Studies), 2015)
The existence of market anomaly patterns in the stock market led to retun the stock is no longer random. This is contrary to the efficient market hypothesis. In the case of mutual fund, a market anomaly attention is january effect where the high returns in January. This market anomaly pattern is one indication of window dressing. In mutual funds, window dressing conducted by fund managers by improving the performance of the portfolio prior to presentation to shareholders. One of the main reasons of window dressing practice on mutual funds are the targets to be achieved each year end. If the target is not reached, there is an attempt to change such that the target is achieved because it affects the increase in managed funds. This study aims to prove whether there is window dressing practise in equity mutual funds in Indonesia. This study was conducted using 22 equity mutual funds in Indonesia from 2008 to 2012. The results of this study indicate that there is a practice of window dressing in the event the period of 20 days compared to 30 days.